Genome evolution in major Escherichia coli O157:H7 lineages - Benson Andrew K; Johnson Roger; Ziebell Kim; Steele Marina; Laing Chad; Zhang Yongxiang; Taboada Eduardo; Gannon Victor PJ (BMC Genomics, 2007)
Abstract Background Genetic analysis of Escherichia coli O157:H7 strains has shown divergence into two distinct lineages, lineages I and II, that appear to have distinct ecological characteristics, with lineage I strains more commonly associated with human disease. In this study, microarray-based comparative genomic hybridization (CGH) was used to identify genomic differences among 31 E. coli O157:H7 strains that belong to various phage types (PTs) and different lineage-specific polymorphism assay (LSPA) types. Results A total of 4,084 out of 6,057 ORFs were detected in all E. coli O157:H7 strains and 1,751 were variably present or absent. Based on this data, E. coli O157:H7 strains were divided into three distinct clusters, which consisted of 15 lineage I (LSPA type 111111), four lineage I/II (designated in this study) (LSPA type 211111) and 12 lineage II strains (LSPA 222222, 222211, 222212, and 222221), respectively. Eleven different genomic regions that were dominant in lineage I strains (present in ≥80% of lineage I and absent from ≥ 92% of lineage II strains) spanned segments containing as few as two and up to 25 ORFs each. These regions were identified within E. coli Sakai S-loops # 14, 16, 69, 72, 78, 83, 85, 153 and 286, Sakai phage 10 (S-loops # 91, 92 and 93) and a genomic backbone region. All four lineage I/II strains were of PT 2 and possessed eight of these 11 lineage I-dominant loci. Several differences in virulence-associated loci were noted between lineage I and lineage II strains, including divergence within S-loop 69, which encodes Shiga toxin 2, and absence of the non-LEE encoded effector genes nleF and nleH1-2 and the perC homologue gene pchD in lineage II strains. Conclusion CGH data suggest the existence of two dominant lineages as well as LSPA type and PT-related subgroups within E. coli O157:H7. The genomic composition of these subgroups supports the phylogeny that has been inferred from other methods and further suggests that genomic divergence from an ancestral form and lateral gene transfer have contributed to their evolution. The genomic features identified in this study may contribute to apparent differences in the epidemiology and ecology of strains of different E. coli O157:H7 lineages.